Public Administration Activities in the Light of the Contemporary Conception of Public Business Law - Rabska, Teresa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of Działania administracji publicznej w świetle współczesnej koncepcji publicznego prawa gospodarczego by Teresa Rabska published originally in Polish in Instrumenty i formy prawne działania administracji gospodarczej by Adam Mickiewiczy University Press in 2009. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administration” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.